Applications of Gene Therapy in Dentistry: A Review Article - Nair, Karthika; Bhat, Amitha Ramesh (Journal of Health and Allied Sciences NU, 2023)
Gene therapy promises to possess a good prospect in bridging the gap between dental applications and medicine. The dynamic therapeutic modalities of gene therapy have been advancing rapidly. Conventional approaches are being revamped to be more comprehensive and pre-emptive, which could do away with the need for surgery and medicine altogether. The complementary base sequences known as genes convey the instructions required to manufacture proteins. The oral cavity is one of the most accessible locations for the therapeutic intervention of gene therapy for several oral tissues. In 1990, the first significant trial of gene therapy was overseen to alleviate adenosine deaminase deficiency. The notion of genetic engineering has become increasingly appealing as a reflection of its benefits over conventional treatment modalities. An example of how this technology may alter dentistry is the implementation of gene therapy for dental and oral ailments. The objective of this article is to examine the effects of gene therapy on the field of dentistry, periodontology and implantology. Furthermore, the therapeutic factors of disease therapy, minimal invasion, and appropriate outcome have indeed been taken into consideration.
Keywords: gene therapy; applications; dentistry; periodontology; recent advances